Towards circular textiles: Life cycle assessment of homewear produced from regenerative cotton and post-industrial waste versus conventional cotton - Teresa M. Mata; Inês Ruge; Hernâni Dias; Isabel Batista; Tércio Pinto; Ricardo Figueiredo; Alberto Figueiredo; António A. Martins (Journal of Cleaner Production, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Cortical volumetry and longitudinal cognitive changes in Parkinson’s disease: insights from the COPPADIS cohort - Tania Álvarez-Avellón; Carmen Solares; Juan Álvarez-Carriles; Pablo Franco-Rosado; Patricia Diaz-Galvan; Diego Santos-García; Pablo Mir; Manuel Menéndez-González; Astrid Adarmes Daniela; Almeria Marta; Maria Gema Alonso Losada; Araceli Alonso Cánovas; et al. (Brain Imaging and Behavior, 2025)
Cognitive decline is a major non-motor symptom in Parkinson’s disease (PD), often linked to brain atrophy. This study examines the relationship between cortical atrophy and age groups in predicting cognitive decline in PD over five years. 188 PD patients from the COPPADIS cohort were stratified by age: young (30–55 years, N = 47), middle-aged (56–65 years, N = 59), and older adults (66–75 years, N = 82). Baseline cortical volume was assessed using T1-weighted MRI, and cognitive decline was evaluated using the annual rate of change of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS). Parametric or non-parametric tests were applied to evaluate group differences. Main analyses consist of several multiple regression analyses to examine associations between baseline brain atrophy and cognitive decline by age group. Older adults exhibited significantly greater cognitive decline in comparison to the younger age groups in the three compose scores of the PDCRS -Fronto-subcortical (H(2) = 41.08, p < 0.001), Posterior Cortical (H(2) = 22.03, p < 0.001), and Total(H(2) = 41.13, p < 0.001). Higher educational level has a significant positive effect on older adults, specifically for working memory performance, delayed verbal memory and the fronto-subcortical composed score. Multiple regression models underscored the predictive value of the bilateral hippocampus, bilateral medial orbitofrontal cortex, right precuneus, and right isthmus cingulate gyrus, together with being an older adult or having a higher education. MRI measures, age, and education predict cognitive decline in PD. Longitudinal assessments are essential for refining atrophy-cognition correlations and optimizing patient stratification.

Effects of light quality and intensity on growth and bromoform content of the red seaweed Asparagopsis taxiformis - Raquel Torres; Ana M. Campos; Jacob Goldman; Isabel Barrote; Leonardo Mata; João Silva (Journal of Applied Phycology, 2024)
Species of the genus Asparagopsis are rich in halogenated bioactive compounds, particularly bromoform. Its use as a feed additive in ruminant livestock drastically decreases the animal’s methane production, thereby reducing the industry’s environmental impact. Addressing the high demand for Asparagopsis biomass requires the understanding of the culture conditions that promote higher growth rates and bromoform content. Here we evaluated how different light quality combinations (High-Blue:Red, Medium Blue:Red, High-Blue:Green:Red, and White) and four light intensities (30, 60, 90 and 120 μmol photons m −2 s −1 ) affect the growth and bromoform content of the Asparagopsis taxiformis tetrasporophyte in indoor tumbling cultures at two biomass densities. We also assessed the effect of light intensity on the photosynthetic response by measuring oxygen evolution rates. Light spectra containing intermediate wavelengths promoted higher growth, regardless of biomass density. Of the different light qualities tested, white light promoted the highest bromoform content. Increasing light intensity led to a positive response in A. taxiformis growth. However, the photosynthetic parameters estimated showed that the two higher light intensity treatments were above the saturation irradiance, for both culture densities. This, along with the observed development of contamination, suggests that long-term cultures of A. taxiformis should be maintained at light intensities no higher than 60 μmol photons m −2 s −1 . In addition, we found that exposing cultures to higher irradiances does not guarantee a bromoform-richer biomass. These results offer valuable insights for optimizing biomass and bioactive compound production in indoor cultures of the Asparagopsis genus.

Effects of solvent extracted organic matter from outdoor air pollution on human type II pneumocytes: Molecular and proteomic analysis - Alejandro Déciga-Alcaraz; Carmen Tlazolteotl Gómez de León; Jorge Morales Montor; Josefina Poblano-Bata; Yadira Margarita Martínez-Domínguez; M. Isabel Palacios-Arreola; Omar Amador-Muñoz; Carolina Rodríguez-Ibarra; Gustavo J. Vázquez-Zapién; Mónica M. Mata-Miranda; Yesennia Sánchez-Pérez; Yolanda I. Chirino (Environmental Pollution, 2023)

DNA metabarcoding to assess prey overlap between tuna and seabirds in the Eastern tropical Atlantic: Implications for an ecosystem-based management - Ana Rita Carreiro; Jaime A. Ramos; Vanessa A. Mata; Nathalie M. Almeida; Isabel Rodrigues; Ivo dos Santos; Diana M. Matos; Pedro M. Araújo; Teresa Militão; Jacob González-Sólis; Vitor H. Paiva; Ricardo Jorge Lopes (Marine Environmental Research, 2023)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

The use of stable and unstable green fluorescent proteins for studies in two bacterial models: Agrobacterium tumefaciens and Xanthomonas campestris pv. campestris - Pilar Sabuquillo; Adela Gea; Isabel M. Matas; Cayo Ramos; Jaime Cubero (Archives of Microbiology, 2017)

Annotation and overview of the Pseudomonas savastanoi pv. savastanoi NCPPB 3335 draft genome reveals the virulence gene complement of a tumour‐inducing pathogen of woody hosts - Pablo Rodríguez‐Palenzuela; Isabel M. Matas; Jesús Murillo; Emilia López‐Solanilla; Leire Bardaji; Isabel Pérez‐Martínez; Martín E. Rodríguez‐Moskera; Ramón Penyalver; Maria M. López; José M. Quesada; Bryan S. Biehl; Nicole T. Perna; et al. (Environmental Microbiology, 2010)
Summary Pseudomonas savastanoi pv. savastanoi is a tumour‐inducing pathogen of Olea europaea L. causing olive knot disease. Bioinformatic analysis of the draft genome sequence of strain NCPPB 3335, which encodes 5232 predicted coding genes on a total length of 5856 998 bp and a 57.12% G + C, revealed a large degree of conservation with Pseudomonas syringae pv. phaseolicola 1448A and P. syringae pv. tabaci 11528. However, NCPPB 3335 contains twelve variable genomic regions, which are absent in all previously sequenced P. syringae strains. Various features that could contribute to the ability of this strain to survive in a woody host were identified, including broad catabolic and transport capabilities for degrading plant‐derived aromatic compounds, the duplication of sequences related to the biosynthesis of the phytohormone indoleacetic acid ( iaaM, iaaH ) and its amino acid conjugate indoleacetic acid‐lysine ( iaaL gene), and the repertoire of strain‐specific putative type III secretion system effectors. Access to this seventh genome sequence belonging to the ‘ P. syringae complex’ allowed us to identify 73 predicted coding genes that are NCPPB 3335‐specific. Results shown here provide the basis for detailed functional analysis of a tumour‐inducing pathogen of woody hosts and for the study of specific adaptations of a P. savastanoi pathovar.